F- + CH3I → FCH3 + I- reaction dynamics: nontraditional atomistic mechanisms and formation of a hydrogen-bonded complex - Zhang, Jiaxu; Mikosch, Jochen; Trippel, Sebastian; Otto, Rico; Weidemüller, Matthias; Wester, Roland; Hase, William L. (The journal of physical chemistry letters, 2010)
Ion imaging experiments and direct chemical dynamics simulations were performed to study the atomic-level dynamics for the F− + CH3I → FCH3 + I− SN2 nucleophilic substitution reaction at 0.32 eV collision energy. The simulations reproduce the product energy partitionings and the velocity scattering angle distribution measured in the experiments. The simulations reveal that the substitution reaction occurs by two direct atomic-level mechanisms, that is, rebound and stripping, and an indirect mechanism. Approximately 90% of the indirect events occur via a prereaction F−···HCH2I hydrogen-bonded complex. This mechanism may play an important role for other F− SN2 reactions due to the strong electronegativity of fluorine. The average product energy partitioning for the F− + CH3I indirect mechanism agrees with the prediction of PST, even though a FCH3···I− postreaction complex is not formed.
Das Minuszeichen im Titel ist hochgestellt, die 3 ist tiefgestellt
Published online 3 September 2010
Gesehen am 22.03.2024